Monitoring creep damage at a weld using a potential drop technique. (June 2017) - Corcoran, J.; Nagy, P.B.; Cawley, P.
Abstract: Welds of high-temperature pressurised components act as preferential sites for creep damage accumulation and will frequently be the life limiting feature. Type IV failures, where cracking occurs between the heat affected zone (HAZ) and parent material, are of particular concern in power station components. Typically damage will be characterised by locally high strain rates in the HAZ and local grain boundary separation leading to crack initiation and growth. A potential drop creep monitoring technique is suggested and demonstrated on cross-weld creep test specimens to be sensitive to both strain and cracking. The technique can be implemented as an array, discretizing a larger area into local measurements, providing contextual information and enabling the identification of local increases in damage. The influence of strain and cracking can be effectively separated to indicate crack initiation. The proposed sensor has very simple and robust high-temperature hardware lending itself to in-situ measurements in the field. Highlights: A potential drop technique is presented which has dual-sensitivity to both the local strain and cracking that is anticipated with creep damage at a weld. Accelerated cross-weld tests demonstrate the sensitivity to damage in advance of failure. A method for separating the influence of strain and cracking is presented. The system is mechanically robust and is low power, lending itself to permanent installation and in situ monitoring.